2018
DOI: 10.1002/ejic.201800038
|View full text |Cite
|
Sign up to set email alerts
|

Group 11 Metal Complexes Coordinated by the (Nitronyl Nitroxide)‐2‐ide Radical Anion: Facile Oxidation of Stable Radicals Controlled by Metal–Carbon Bonds in Radical‐Metalloids

Abstract: A series of group 11 metal complexes coordinated by (nitronyl nitroxide)-2-ide radical anion NN-M(dtpb) [NN: nitronyl nitroxide; M: Cu I , Ag I , and Au I ; dtpb: 1,2-bis(di-2-tolylphosphanyl)benzene)] was prepared. Their structures, electrochemical properties, and related theoretical calculations were investigated. The oxidation potential (E ox , V vs. Fc/Fc + ) of the NN-moiety in these radical-metalloids significantly shifted to the negative direction in comparison to that of the unsubsti- [a] Preparation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…We have previously reported that NN‐metal complex NN‐M‐L exhibited unique electrochemical behaviors in which the oxidation potential assignable to the NN moieties shifted abnormally to a negative potential [11c,12] . We also measured the cyclic voltammograms (CVs) of (NN‐Au) 2 ‐1 o , m , p and (NN‐Au) 3 ‐2 to investigate their electrochemical properties and to determine the effect of aurophilic interactions (Figures 8 and S5, and Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously reported that NN‐metal complex NN‐M‐L exhibited unique electrochemical behaviors in which the oxidation potential assignable to the NN moieties shifted abnormally to a negative potential [11c,12] . We also measured the cyclic voltammograms (CVs) of (NN‐Au) 2 ‐1 o , m , p and (NN‐Au) 3 ‐2 to investigate their electrochemical properties and to determine the effect of aurophilic interactions (Figures 8 and S5, and Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Third, the second oxidation potential of (NN‐Au) 2 ‐1 o was slightly higher than the oxidation potentials of (NN‐Au) 2 ‐1 m and (NN‐Au) 2 ‐1 p . We have reported that the oxidation potentials assignable to the NN moieties in NN‐M‐L are correlated with the natural population analysis (NPA) charges at the C2 carbon atom in the NN moiety [12] . The particular differences in the electrochemical properties of (NN‐Au) 2 ‐1 o suggest higher electron‐donating ability due to the aurophilic interaction, which causes a large negative and a small positive NPA charge compared with (NN‐Au) 2 ‐1 p (Table S8).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The synthetic route for Gd 3+ ·(1 – ) 3 is shown in Scheme . This method is similar to our previously reported method for preparing a series of organometallic nitronyl nitroxide (NN) radicals. , After the generation of an NN anion upon treatment of NN-H with sodium hydroxide, the resulting mixture was allowed to react with AuCl­(THT) (THT = tetrahydrothiophene) to afford Na + ·1 – (CCDC 2090754). Compound Na + ·1 – was converted to Gd 3+ ·(1 – ) 3 by treatment with gadolinium­(III) nitrate.…”
mentioning
confidence: 79%
“…The design of organometallic derivatives of nitroxide radicals [ 1 , 2 , 3 ] has a high potential for the development of new organic synthesis principles and the study of the mechanisms of catalytic reactions [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ] as well as for the creation of polyfunctional magnetoactive materials exhibiting diverse intra- and intermolecular interactions and spin-exchange coupling [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ,…”
Section: Introductionmentioning
confidence: 99%